From Disruption to Collision : the New Competitive Dynamics - Iansiti, Marco; Lakhani, Karim (MIT Sloan Management Review, 2020)
Collisions between innovators and established players are forcing leaders of existing companies to reexamine how they do business in settings where new players follow radically different rules. For many, making small or incremental changes won't be enough. They will need to fundamentally alter their operating models, including how they gather and respond to information and how they interact with their customers.